Optimalisasi Umur Pemakaian AC Melalui Sistem Informasi Reminder Perawatan - Aries Setiawan; Sasono Wibowo; Ida Farida (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
There is no periodic scheduling of Air Conditioner (AC) maintenance, which stems from the lack of recording on the maintenance card and maintenance book, resulting in a lot of AC damage that propagates from one component to component until finally the AC cannot function completely. A system is needed to provide information that will remind the time of maintenance as the first step in optimizing the life of the air conditioner. The purpose of this study is to build an information system of maintenance-reminder, so that the air conditioner used is maintained according to a predetermined schedule. The method used to build this system is a waterfall with five steps, namely: analysis, design, implementation, and testing. To Test the system that has been made, in this study using black box-testing by checking every part of each system. Our findings are to produce a standardized maintenance reminder system. The test results show that all components in the system are functioning properly, so it is easier for users to know which air conditioners need maintenance. With this system, it can maximize the maintenance function to optimize service life.